2016
DOI: 10.1017/s0950268816001382
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of interferon-gamma release assays for tuberculosis screening in nursing homes

Abstract: Tuberculosis (TB) in older people is a significant public health problem in low TB-incidence countries. Older persons have increased TB incidence, higher reactivation and mortality. A delay in diagnosis and initiation of TB treatment in patients with atypical clinical and radiological features is a significant factor of widespread transmission. This study aimed to evaluate the cost-effectiveness of interferon-gamma release assays [IGRAs; QuantiFERON®-TB Gold In-Tube (QFT) and T-SPOT®.TB (T-SPOT)] compared to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…When comparing the modeling results for four possible screening strategies, Li et al found that the most cost-effective strategy was LTBI/TB screening, providing the highest Life Years (LYs) and QALYs gained (8). Results from Kowada's modeling were similar, finding that the most cost-effective TB screening practice was QuantiFERON ($ 50,000 US/QALY), while TST (tuberculin skin test) followed by QFT was best for residents considered to be higher risk of TB reactivation due to comorbidities, such as HIV infection, diabetes mellitus and chronic kidney disease (9).…”
Section: Assessment Of Cxr and Other Methods To Screen For Tb In Ltcfmentioning
confidence: 92%
See 1 more Smart Citation
“…When comparing the modeling results for four possible screening strategies, Li et al found that the most cost-effective strategy was LTBI/TB screening, providing the highest Life Years (LYs) and QALYs gained (8). Results from Kowada's modeling were similar, finding that the most cost-effective TB screening practice was QuantiFERON ($ 50,000 US/QALY), while TST (tuberculin skin test) followed by QFT was best for residents considered to be higher risk of TB reactivation due to comorbidities, such as HIV infection, diabetes mellitus and chronic kidney disease (9).…”
Section: Assessment Of Cxr and Other Methods To Screen For Tb In Ltcfmentioning
confidence: 92%
“…Kowada ran a similar modeling experiment in 2016 (also with a threshold for cost-effectiveness of $50,000 per QALY gained) for a hypothetical population of 84 years-old LTCF residents in Japan with previous BCG vaccination. Of seven possible screening strategies, using CXR alone was found to be the least cost-effective means to find new TB cases (9). Also in Japan, Kowada et al (10) modeled a hypothetical cohort of immunocompetent and 65 years-old people using three different strategies.…”
Section: Cost-effectiveness Of Screening Using Cxr To Find Active Tb Casesmentioning
confidence: 99%
“…Four previous cost-effectiveness studies of TB have been reported to compare screening strategies with no screening in the elderly [ 31 33 , 72 ]. Two of them demonstrated that TST screening was more cost-effective than no screening and CXR screening in long-term care facilities for the elderly in Canada [ 31 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The other two studies in Japan BCG-vaccinated elderly and nursing homes demonstrated that QFT-GIT screening was the most cost-effective among screening strategies by TST, CXR and other products of IGRAs [ 32 , 72 ]. The sensitivity of IGRA, prevalence of LTBI and TB, and BCG rate in TST screening were the influential variables [ 32 , 72 ]. The uncertainty of these variables were not significantly observed in our study because of the higher prevalence rates in Hong Kong RCHEs and the exclusion of TST.…”
Section: Discussionmentioning
confidence: 99%
“…LTBI testing guidelines may be difficult to follow in practice, and simplification of these might improve testing rates. Recent data suggest that IGRA testing may be most cost‐effective for this population . The high prevalence of LTBI in these LTCFs underscores the need to address whether to treat such individuals—for their own health as well as the benefit of other LTCF residents.…”
Section: Discussionmentioning
confidence: 99%